A National Multicenter Study on Initial Antiviral Treatment Preferences on Chronic Hepatitis B: Entecavir Versus Tenofovir Disoproxil Fumarate - Yamazhan, Tansu; Zerdali, Esra; Önlen, Yusuf; Tosun, Selma; Günal, Özgür; Batırel, Ayşe; Hasanoğlu, İmran; Turunç, Tuba; Balcı, Umay; Kaya, Sibel Yıldız; Karabay, Oğuz; Yıldız, İlknur Esen; et al. (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Selecting the initial antiviral regimen for chronic hepatitis B (CHB) requires balancing patients’ comorbidities and long-term safety. This study examines differences in patient and disease-related factors that guide clinicians to prescribe either ente cavir (ETV) or tenofovir disoproxil fumarate (TDF) as the initial treatment. Materials and Methods: The study included treatment-naïve CHB patients aged 18 or older who had been diagnosed for at least 1 year since 2010 and initiated on antiviral therapy. The data included variables such as age, gender, body mass index (BMI), comorbidities, liver disease activity, biopsy results, cirrhosis, hepatic steatosis, hepatitis B e-antigen status, hepatitis B virus DNA levels, triglycerides, cholesterol, renal function, and baseline bone mineral density (BMD), which were assessed by dual-energy x-ray absorptiometry (DEXA). Results: Among 2259 patients (61.6% male), 1270 patients (56.22%) received TDF, while 989 patients (43.78%) received ETV as first line therapy. The TDF was more commonly prescribed to patients with a lower BMI (median